2019
DOI: 10.1096/fj.201901478rr
|View full text |Cite
|
Sign up to set email alerts
|

Wnt4‐modified NSC transplantation promotes functional recovery after spinal cord injury

Abstract: Spinal cord injury (SCI) can lead to severe motor and sensory dysfunction, yet there are no effective therapies currently due to the failure of reconstructing the interruption of the neuroanatomical circuit. While neural stem cell (NSC) transplantation has been considered a potential strategy to repair the neural circuit after SCI, the efficacy of this strategy remains unproven. The main reason is that most of the transplanted NSC differentiates into astrocyte rather than neuron in the microenvironment of SCI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 36 publications
(140 reference statements)
1
55
0
Order By: Relevance
“…NSCs were obtained from the fetal brain of embryonic day 14 rats, which were extracted from pregnant Sprague-Dawley (SD) rats (Laboratory Animal Center of Sun Yat-Sen University, Guangzhou, China) [27][28][29] . NSCs were plated in a T25 culture flask (Corning, Acton, MA, 430639) containing maintenance medium consisting of Dulbecco's modified Eagle's medium/F12 nutrient mixture, 2% B27, 1% penicillin/streptomycin, 1% L-glutamine (Invitrogen, Carlsbad, CA, 11320033), 20 ng/mL fibroblast growth factor-2 (FGF-2) and 20 ng/mL epidermal growth factor (EGF) (PeproTech, Rocky Hill, NJ, 96-400-29, 96-AF-100-15).…”
Section: Nsc Isolation and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…NSCs were obtained from the fetal brain of embryonic day 14 rats, which were extracted from pregnant Sprague-Dawley (SD) rats (Laboratory Animal Center of Sun Yat-Sen University, Guangzhou, China) [27][28][29] . NSCs were plated in a T25 culture flask (Corning, Acton, MA, 430639) containing maintenance medium consisting of Dulbecco's modified Eagle's medium/F12 nutrient mixture, 2% B27, 1% penicillin/streptomycin, 1% L-glutamine (Invitrogen, Carlsbad, CA, 11320033), 20 ng/mL fibroblast growth factor-2 (FGF-2) and 20 ng/mL epidermal growth factor (EGF) (PeproTech, Rocky Hill, NJ, 96-400-29, 96-AF-100-15).…”
Section: Nsc Isolation and Culturementioning
confidence: 99%
“…To induce neuronal differentiation, cells were plated at a density of 2 × 10 5 cells/well in 6-or 12-well tissue culture plates and allowed to adhere for 24 h at 37°C, at which time cells were switched to neuronal differentiation medium consisting of basic medium supplemented with 2% B27, 1% penicillin/streptomycin, and 1% l-glutamine. The medium was changed every 2-3 days 29 .…”
Section: Nsc Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…A number of clinical trials have reported the efficacy of the stem cell transplantation as a potential strategy to repair damaged tissue and recover locomotor functional after SCI (15,35,36). These studies demonstrated that the transplanted cells differentiate into neurons, which mainly rebuilt neural circuits to promote tissue repair and locomotor function recovery (37).…”
Section: Discussionmentioning
confidence: 99%
“…To induce neural differentiation, cells were plated at a density of 2x10 5 cells/well in 6-or 12-well tissue-culture plates and allowed to adhere for 24 h at 37˚C, at which time cells were switched to neural differentiated medium consisting of basic medium supplemented with 2% B27, 1% penicillin/streptomycin and 1% l-glutamine. The medium was changed every 2-3 days (14,15).…”
Section: Methodsmentioning
confidence: 99%